Cardiac Tolerability of Pertuzumab Plus Trastuzumab Plus Docetaxel in Patients With HER2‐Positive Metastatic Breast Cancer in CLEOPATRA: A Randomized, Double‐Blind, Placebo‐Controlled Phase III Study. (8th March 2013) - Swain, Sandra M.; Ewer, Michael S.; Cortés, Javier; Amadori, Dino; Miles, David; Knott, Adam; Clark, Emma; Benyunes, Mark C.; Ross, Graham; Baselga, José
Abstract : Introduction: We report cardiac tolerability of pertuzumab plus trastuzumab plus docetaxel versus placebo plus trastuzumab plus docetaxel observed in the phase III study CLEOPATRA in patients with HER2‐positive first‐line metastatic breast cancer (MBC). Patients and Methods: Left ventricular ejection fraction (LVEF) ≥50% and ECOG performance status of 0 or 1 were required for study entry. During the study, LVEF assessments took place every 9 weeks. Pertuzumab/placebo was given at 840 mg, then 420 mg q3w; trastuzumab was administered at 8 mg/kg, then 6 mg/kg q3w, and docetaxel was initiated at 75 mg/m 2 q3w. Results: The incidence of cardiac adverse events (all grades) was 16.4% in the placebo arm and 14.5% in the pertuzumab arm, with left ventricular systolic dysfunction (LVSD, all grades) being the most frequently reported event (8.3% versus 4.4% in the placebo and pertuzumab arm). Declines in LVEF by ≥10% points from baseline and to <50% were reported in 6.6% and 3.8% of patients in the placebo and pertuzumab arm, respectively. Seventy‐two percent (placebo arm) and 86.7% (pertuzumab arm) of those patients recovered to a value ≥50%. The incidence of symptomatic LVSD was low, occurring in 1.8% ( n = 7) versus 1.0% ( n = 4) of patients in the placebo and pertuzumab arm. In 8/11 patients, the symptomatic LVSD had resolved at data cutoff. Conclusion: The combination of pertuzumab plus trastuzumab plus docetaxel did not increase the incidence of cardiac adverse events, including LVSD, compared with the control arm in HER2‐positive MBC. The majority of cardiac adverse events were reversible. Abstract : Tolerability of pertuzumab plus trastuzumab plus docetaxel versus placebo plus trastuzumab plus docetaxel was observed in patients with HER2‐positive metastatic breast cancer. Declines in LVEF were reported and the incidence of symptomatic LVSD was low. The majority of cardiac adverse events were reversible. Abstract : 摘要 引言 . 本文报道III期CLEOPATRA研究中帕妥珠单抗、曲妥珠单抗和多西他赛联合治疗对比安慰剂、曲妥珠单抗和多西他赛联合一线治疗HER2阳性转移性乳腺癌（MBC）患者的心脏耐受性。 患者和方法 . 入选患者要求左心室射血分数（LVEF）≥50%且ECOG体能状态为0或1分。研究期间，LVEF每9周评估一次。帕妥珠单抗/安慰剂起始剂量840mg，随后每3周一次，每次420 mg；曲妥珠单抗起始剂量8mg/kg，随后每3周一次，每次6mg/kg；多西他赛起始剂量75mg/m 2 ，每3周一次。 结果 . 安慰剂组心脏不良事件发生率（所有级别）为16.4%，帕妥珠单抗组为14.5%，左心室收缩功能障碍（LVSD，所有级别）是最常见的不良事件（安慰剂组8.3%vs.帕妥珠单抗组4.4%）。与基线时相比LVEF降低≥10%（绝对值）且降至<50%者，在安慰剂组和帕妥珠单抗组分别为6.6%和3.8%。其中各有72%（安慰剂组）和86.7%（帕妥珠单抗组）的患者LVEF恢复至≥50%。有症状的LVSD发生率低，安慰剂组为1.8%（7例），帕妥珠单抗组为1.0%（4例）。数据截止时，11例患者中，8例LVSD症状得到缓解。 结论 . 在HER2阳性MBC患者中，与对照组相比，帕妥珠单抗、曲妥珠单抗和多西他赛联合治疗并未增加包括LVSD在内的心脏不良事件发生率。多数心脏不良事件是可逆的。